Effect of plant spacing and salinity of irrigation water on growth and flower yield of marigold in semi-arid conditions - Chauhan, S.K. (Annals of Agricultural Research, 2016)
A field experiment was carried out during rabi seasons of 2011-12 and 2012-13 at R.B.S.College research farm, Bichpuri, Agra to assess the effect of planting spacing and irrigation water salinity on behavior of African marigold (Tagetes erecta Linn) cv. ’Pusa Narangi’. Maximum plant height and secondary branches plantâ€“1 increased at closer spacing of 50 cm Ã— 40 cm; however, spread and diameter of plant, primary branches plantâ€“1 increased in wider spacing (50 cm Ã— 50 cm). Opening of first flower was delayed in closer spacing, whereas duration of flowering and yield 0.41 kg plantâ€“1 was observed in wide spacing (50 cm Ã— 50 cm) but yield 202.8 q haâ€“1 obtained in closer spacing (50 cm Ã— 40 cm). The use of saline water in irrigation increase salinity levels reduced plant height; plant spared, and yields of flower 125.1 q haâ€“1 in ECiw 9 dS/m. Interaction between spacing and salinity levels was found non-significant in all characteristics. The net profit was maximum in (50 cm Ã— 40 cm) row spacing (Rs. 50,120) and minimum in row spacing (50 cm Ã— 50 cm) (Rs. 45,920). In case of salinity the maximum net profit obtained in best available water (Rs. 51,320) and lowest in Eciw 9 dS/m (Rs. 19,000) respectively.